Profil Sikap Guru Terhadap Kegiatan Revitalisasi Dan Reedukasi Pendidikan Agama Dan Nilai Sosial Budaya Bugis Makassar Kepada Murid SD di Kota Makassar - Hadis, Abdul; Murni, ST; Nurhayati, Nurhayati (Universitas Negeri Makassar, 2017)
Elementary age is an age where children easily imitate what adults do in family, school, and community. The rise of the symptoms of radicalism, extremism, terrorism, and liberalism in the life of society, nation and state today, is a social phenomenon that must be prevented and overcome. These four understandings all lead people to behave criminally. Therefore, one of the efforts that can be done to save the young generation, especially the elementary school students in Makassar is teachers, parents, community, religious leaders, community leaders, and city government, need to do revitalization and reedukasi religious education and social value Bugis Makassar culture to elementary school students.